Performance evaluation of improved cook stoves (ICS) disseminating in Bangladesh - Islam, MS; Khanam, M; Rouf, MA; Rahaman, M (Bangladesh Journal of Scientific and Industrial Research, 2015)
This paper describes the monitoring and evaluation of three improved cook stove (ICS) provided by GIZ, which were they disseminated throughout the Bangladesh. The project assessed stove performance using lab-based water boiling tests (WBTs), which yield a number of performance indicators including time to water boil, specific fuel consumption, average fire power and energy efficiency when the stove is operated at both high and low power output. In all cases, ICSs were compared to local traditional cook stoves (TCSs). The results of the WBTs were mixed. Although the improved stoves generally showed some improvement in efficiency for the low-power simmering phases, the stoves were less efficient than traditional stoves in high-power water-boiling phases. Three ICS models and one traditional stove were tested and compared. Results from this study provide stove performance information to practitioners disseminating stove technology in the field. DOI: http://dx.doi.org/10.3329/bjsir.v49i4.22624 Bangladesh J. Sci. Ind. Res. 49(4), 219-226, 2014